2017
DOI: 10.1055/s-0037-1603929
|View full text |Cite
|
Sign up to set email alerts
|

The IMPROVEDD VTE Risk Score: Incorporation of D-Dimer into the IMPROVE Score to Improve Venous Thromboembolism Risk Stratification

Abstract: Background The IMPROVE score is a validated venous thromboembolism (VTE) assessment tool to risk stratify hospitalized, medically ill patients based on clinical variables. It was hypothesized that addition of D-dimer measurement to derive a new IMPROVEDD score would improve identification of at risk of VTE. Methods The association of the IMPROVE score and D-dimer ≥ 2 × the upper limit of normal (ULN) with the risk of symptomatic deep vein thrombosis, nonfatal pulmonary embolism, or VTE-related deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
103
1
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 24 publications
(28 reference statements)
3
103
1
12
Order By: Relevance
“…14,15,17,27,28 The present study demonstrated that the addition of albumin to validated risk assessment models (such as the IMPROVE score or Padua score) improved their performance in risk discrimination and reclassification. 14,15,17,27,28 The present study demonstrated that the addition of albumin to validated risk assessment models (such as the IMPROVE score or Padua score) improved their performance in risk discrimination and reclassification.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…14,15,17,27,28 The present study demonstrated that the addition of albumin to validated risk assessment models (such as the IMPROVE score or Padua score) improved their performance in risk discrimination and reclassification. 14,15,17,27,28 The present study demonstrated that the addition of albumin to validated risk assessment models (such as the IMPROVE score or Padua score) improved their performance in risk discrimination and reclassification.…”
Section: Discussionmentioning
confidence: 59%
“…Several risk assessment models have been developed to identify hospitalized patients at risk of VTE. 14,15,17,27,28 The present study demonstrated that the addition of albumin to validated risk assessment models (such as the IMPROVE score or Padua score) improved their performance in risk discrimination and reclassification. These findings suggest that laboratory tests or biomarkers may be used in conjunction with risk assessment models comprised of clinical variables to refine VTE prediction.…”
Section: Refinement Of Vte Risk Prediction By Albuminmentioning
confidence: 59%
See 2 more Smart Citations
“…6 The IMPROVEDD VTE risk score shows how incorporation of D-Dimer into the IMPROVE score would improve venous thromboembolism risk stratification. 7 Impact of venous thromboembolism on the formation and progression of carotid atherosclerosis is also demonstrated from the Tromsø Study.…”
mentioning
confidence: 94%